Effect of functionalisation on polysulfone-based ultrafiltration membranes. (1st July 2010) - Raj, S. Anitha; Rajesh, S.; Lakshmi, K.; Shobana, K.H.; , D. Mohan
Polysulfone membranes possess excellent mechanical, biological and chemical stability but they suffer from fouling which leads to flux decline. Fouling can be minimised by functionalisation. In an attempt to overcome this limitation, the polysulfone was both sulphonated and carboxylated. The presence of sulphonic and carboxylic groups was confirmed through IR and NMR studies. Incorporation of sulphonic and carboxylic groups in the polymeric chain increases the hydrophilic nature of the membrane as well as the thermal stability, chemical tolerance, mechanical strength, etc. It was observed that the Pure Water Flux (PWF) value of CPSf was greater than that of SPSf and PSf. The actual angle of inclination of the two rings depends on the nature and number of substituent groups. In CPSf the angle of inclination of the two rings is higher than in SPSf. This results in the chains moving apart from each other in the case of CPSf, which could explain its higher flux.